Leadership of the Kiai in Building a Culture of Discipline in the Santri Organization of Pondok Pesantren Rafah (OSPERA) at Pondok Pesantren Rafah Bogor - Muzakir, Muchammad Ibnu; Kurniawan, Muhammad Irfanudin; Robbani, Asub; Rokimin (STIT Fatahillah, 2025)
The highest authority in an Islamic boarding school organization is the leadership or commonly called Kiai. There are various types of Kiai leadership, including charismatic, transformational and autocratic. The object of this research is the Rafah Islamic Boarding School, where the Kiai at this object plays a role as a central figure in building the Islamic boarding school's organizational culture of discipline. The research method used was descriptive qualitative by conducting observations, interviews and documentation of a number of informants including the Education Bureau, the student organization and several other students outside the organization. The research results obtained were that Kiai Rafah agreed to the rules and prohibitions in student discipline by positioning himself as that party, such as the obligation to pray in congregation at the mosque. When implementing these rules, he also set an example by carrying out this habit at all times, namely praying in congregation. Likewise with other rules. This habit is what generates a culture of discipline among organizational members in the Islamic boarding school, both the Islamic boarding school management and the Islamic boarding school organization. Apart from being an exemplary example in implementing discipline, Kiai Pondok Pesantren Rafah's other roles are as an educator, as a religious leader, as a social servant, as a caregiver and guide, and as a Koran teacher. Kiai Pondok Pesantren Rafah also involved members of the Islamic boarding school organization in deliberations with considerations for the future progress of the Islamic Boarding School, he listened to suggestions from the staff under him. If the suggestion is good for the Islamic boarding school, then he will consider the suggestions from his subordinates. He did this solely to achieve what had been the goal of this Pondok since its inception.